Pengaruh Live Streaming dan Electronic Word of Mouth (E-WOM) terhadap Purchase Decision melalui Purchase Intention pada Pengguna TikTok Shop - Immelda Apriliani; Nurul Komariyatin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze the effect of live streaming and electronic word of mouth (e-WOM) on purchase decisions through purchase intention among TikTok Shop users. The research employed a quantitative approach using Partial Least Squares-Structural Equation Modeling (PLS-SEM) with 162 respondents. The results indicate that live streaming has a positive and significant effect on purchase decisions but does not significantly influence purchase intention. In contrast, e-WOM has a positive and significant effect on both purchase intention and purchase decisions. Furthermore, purchase intention significantly and positively affects purchase decisions, confirming its role as a mediating variable. These findings suggest that while live streaming directly influences purchase decisions, e-WOM plays a more dominant role in shaping consumers’ purchase intentions.